A high-toughness and high-permeability PMMA-SAN alloy material and preparation method thereof

Through the preparation method of modified PMMA resin, combined with SAN resin and modified silica, the low impact strength problem of PMMA-SAN alloy material is solved, and the coordinated improvement of high toughness and high transparency is achieved, which significantly improves the overall material. performance.

CN118852829BActive Publication Date: 2024-12-17HEFEI COBEL ADVANCED PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411324187.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-17
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The impact strength of PMMA-SAN alloy materials is low, which limits its application range and is a brittle resin, making it difficult to improve toughness while maintaining high transparency.

Method used

The preparation method of modified PMMA resin includes the esterification reaction of polyethylene glycol-4000, triethylamine and methacryloyl chloride to form intermediate A and react with p-toluene isocyanate and hydroxyethyl methacrylate to form intermediate Body B is finally copolymerized with methyl methacrylate to form a modified PMMA resin with soft and hard segments, combined with SAN resin and modified silica, and blended to enhance toughness.

Benefits of technology

It significantly improves the impact strength and toughness of PMMA-SAN alloy material, while maintaining high transparency and good light transmittance, improving overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of polymer materials, and in particular to a high-toughness and high-permeability PMMA-SAN alloy material and a preparation method thereof, which comprises, by weight, 40-60 parts of modified PMMA resin, 30-40 parts of SAN resin, 1-3 parts of modified silicon dioxide, 0.1-1 parts of primary antioxidants, 0.1-1 parts of secondary antioxidants, and 0.1-1 parts of lubricants. Compared with the prior art, the present invention has the beneficial effects that the alloy material prepared by the present invention has excellent performance in tensile strength, elongation at break, impact strength, and light transmittance, and compared with the traditional PMMA-SAN material, it maintains a high degree of transparency while greatly improving the toughness of the alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a PMMA-SAN alloy material with high toughness and high permeability and a preparation method thereof. Background Art

[0002] Polymethyl methacrylate (PMMA) is a highly transparent polymer resin. It is widely used in aerospace, construction, packaging and other fields due to its good transparency, weather resistance, electrical insulation and processing properties. However, PMMA also has obvious disadvantages, such as brittleness, poor toughness and high cost, which limit its wide application.

[0003] Acrylonitrile-styrene copolymer (AS resin, also known as SAN) is a high-gloss, highly transparent resin with good heat resistance, corrosion resistance and mechanical properties. Its disadvantage is high brittleness, which greatly limits its application range. Currently, SAN resin is mostly used for blending and producing ABS products, and a small number of products are directly injection molded and used in daily necessities, automobiles, home appliances and other industries.

[0004] Both PMMA and SAN resins are highly transparent resins with similar refractive indices and good compatibility, but both are brittle resins. The impact strength of PMMA-SAN alloy materials is low. Therefore, it is necessary to develop a method to ensure the high transparency of PMMA-SAN alloy while significantly improving the toughness of the alloy material. Summary of the invention

[0005] In order to solve the problems mentioned in the above background technology, the present invention provides a PMMA-SAN alloy material with high toughness and high permeability and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a high-toughness and high-permeability PMMA-SAN alloy material, which comprises, by weight, 40-60 parts of modified PMMA resin, 30-40 parts of SAN resin, 1-3 parts of modified silica, 0.1-1 parts of primary antioxidant, 0.1-1 parts of secondary antioxidant, and 0.1-1 parts of lubricant;

[0008] The modified PMMA resin is prepared by the following method:

[0009] Polyethylene glycol-4000 and triethylamine are dispersed in a chloroform-acetone mixed solvent, and a mixed solution of methacryloyl chloride and chloroform is added dropwise to react to obtain an intermediate A;

[0010] Dispersing p-toluene isocyanate, hydroxyethyl methacrylate, and a catalyst, dibutyltin dilaurate, in toluene, and reacting to obtain an intermediate B;

[0011] The intermediate A, the intermediate B and methyl methacrylate are uniformly mixed, and azobisisobutyronitrile is added to carry out polymerization to obtain a modified PMMA resin.

[0012] Preferably, the preparation method of the modified silicon dioxide is as follows:

[0013] Silicon dioxide is added to an ethanol aqueous solution, vinyltriethoxysilane is added, and the mixture is heated for reaction to obtain modified silicon dioxide.

[0014] Preferably, the molar ratio of polyethylene glycol-4000, triethylamine and methacryloyl chloride is 1:(2.5-3.5):(1.8-2.2).

[0015] Preferably, the molar ratio of toluene isocyanate to hydroxyethyl methacrylate is 1:(0.95-1.05).

[0016] Preferably, the added amount of dibutyltin dilaurate is 1%-3% of the total mass of toluene isocyanate and hydroxyethyl methacrylate.

[0017] Preferably, the mass ratio of the intermediate A, intermediate B and methyl methacrylate is (20-40):(5-15):100.

[0018] Preferably, the added amount of azobisisobutyronitrile is 0.1%-1% of the total mass of intermediate A, intermediate B and methyl methacrylate.

[0019] Preferably, the mass ratio of silicon dioxide to vinyltriethoxysilane is 1:(0.05-0.15).

[0020] A second aspect of the present invention provides a method for preparing the above alloy material, comprising the following steps:

[0021] The modified PMMA resin, SAN resin, modified silicon dioxide, a primary antioxidant, a secondary antioxidant and a lubricant are premixed, and the premixed materials are sent to a twin-screw extruder for extrusion granulation to obtain the alloy material.

[0022] Preferably, the parameters of the twin-screw extruder are: temperature settings: zone 1 120±10℃, zone 2 220±10℃, zone 3 230±10℃, zone 4 230±10℃, zone 5 240±10℃, zone 6 240±10℃, zone 7 240±10℃, zone 8 240±10℃, zone 9 245±10℃, die head 250±10℃; main engine speed: 30±3Hz; feeding speed: 12±2Hz; vacuum: -0.07±0.03MPa.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention performs an esterification reaction on polyethylene glycol-4000 and methacrylic acid chloride to obtain an intermediate A containing a double bond and a flexible polyether segment; performs a reaction on p-toluene isocyanate and hydroxyethyl methacrylate to obtain an intermediate B containing a double bond, a rigid benzene ring and an amino ester; then copolymerizes the intermediate A, the intermediate B and methyl methacrylate to obtain a modified PMMA resin; and finally, the modified PMMA resin, SAN resin and modified silica are blended to obtain a PMMA-SAN alloy material with high toughness and high permeability.

[0025] 2. The molecular chain of the modified PMMA resin of the present invention includes a long-chain polyether as a soft segment and a hard segment formed by a rigid benzene ring and an urethane bond. The ether group as the soft segment is easier to rotate, has good flexibility, and plays a toughening role. The rigid benzene ring and urethane bond can improve the impact strength. At the same time, the modified silica, long-chain polyether, and urethane bond can interact with the polar group carbonyl on PMMA to form hydrogen bonds. Since the bond energy of the hydrogen bond is large, the interaction force between the molecules is also increased, which effectively strengthens the interaction force between the molecular chains, thereby improving the impact strength of PMMA.

[0026] 3. The modified PMMA resin of the present invention has similarities with SAN in structure, for example, both have benzene rings, have good compatibility, and maintain good light transmittance after blending.

[0027] 4. It was found that under the system of the present invention, the addition of a small amount of modified silicon dioxide significantly improved the overall performance of the alloy material, while the light transmittance remained good. DETAILED DESCRIPTION

[0028] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0029] Among them, PMMA resin, brand: CM207, manufacturer: Chimei, Taiwan, China;

[0030] SAN resin, brand: PN107, manufacturer: Chi Mei, Taiwan, China;

[0031] Main antioxidant: 1076, manufacturer: BASF;

[0032] Secondary antioxidant: 608, manufacturer: BASF;

[0033] Lubricant: Indonesia EBS, brand: P130;

[0034] Preparation of intermediate A:

[0035] Disperse (0.1 mol, 400 g) polyethylene glycol-4000 and (0.3 mol, 30.3 g) triethylamine in 1 L of chloroform-acetone (chloroform, acetone volume ratio 8:2) mixed solvent, add (0.2 mol, 20.8 g) of methacryloyl chloride and 100 mL of chloroform mixed solution dropwise at 0 °C, control the dropping time to be 1 h, react for 1 h after the addition is completed, heat to 25 °C and continue to react for 10 h, wash with 1 mol / L hydrochloric acid aqueous solution, wash with saturated brine, remove the solvent, and dry to obtain intermediate A.

[0036] Preparation of intermediate B:

[0037] Disperse (0.1 mol, 13.3 g) p-toluene isocyanate, (0.1 mol, 13 g) hydroxyethyl methacrylate, and 0.3 g catalyst dibutyltin dilaurate in 200 ml toluene, stir evenly, keep warm at 60°C for 3 h, filter, wash with saturated brine, remove the solvent, and dry to obtain intermediate B.

[0038] Preparation of modified silica:

[0039] 100 g of silica (particle size: 100 nm) was added to 1 L of 70% by mass ethanol aqueous solution, heated to 50° C. with stirring, 10 g of vinyltriethoxysilane was added, stirred and reacted at 55° C. for 2 h, and dried to obtain modified silica.

[0040] Preparation Example 1

[0041] Preparation of modified PMMA (polymethyl methacrylate) resin

[0042] 30g of intermediate A, 10g of intermediate B and 100g of methyl methacrylate were mixed evenly, 0.5g of azobisisobutyronitrile was added, and prepolymerization was carried out at 85°C for 2h, 45°C for 5h, 60°C for 2h, 80°C for 4h and 100°C for 2h to obtain modified PMMA resin.

[0043] Preparation Example 2

[0044] The difference between this preparation example and preparation example 1 is that 20 g of intermediate A, 10 g of intermediate B, and 100 g of methyl methacrylate are uniformly mixed;

[0045] The rest is exactly the same as Preparation Example 1.

[0046] Preparation Example 3

[0047] The difference between this preparation example and preparation example 1 is that 40 g of intermediate A, 10 g of intermediate B, and 100 g of methyl methacrylate are uniformly mixed;

[0048] The rest is exactly the same as Preparation Example 1.

[0049] Preparation Example 4

[0050] The difference between this preparation example and preparation example 1 is that 20 g of intermediate A, 5 g of intermediate B, and 100 g of methyl methacrylate are uniformly mixed;

[0051] The rest is exactly the same as Preparation Example 1.

[0052] Preparation Example 5

[0053] The difference between this preparation example and preparation example 1 is that 20 g of intermediate A, 15 g of intermediate B, and 100 g of methyl methacrylate are uniformly mixed;

[0054] The rest is exactly the same as Preparation Example 1.

[0055] Preparation Example 6

[0056] The difference between this preparation example and preparation example 1 is that 0 g of intermediate A, 10 g of intermediate B, and 100 g of methyl methacrylate are uniformly mixed;

[0057] The rest is exactly the same as Preparation Example 1.

[0058] Preparation Example 7

[0059] The difference between this preparation example and preparation example 1 is that 20 g of intermediate A, 0 g of intermediate B, and 100 g of methyl methacrylate are mixed uniformly;

[0060] The rest is exactly the same as Preparation Example 1. Example 1

[0061] A high-toughness and high-permeability PMMA-SAN alloy material, comprising, by weight, 50 parts of modified PMMA resin (obtained in Preparation Example 1), 35 parts of SAN resin, 2 parts of modified silicon dioxide, 0.2 parts of a primary antioxidant, 0.4 parts of a secondary antioxidant, and 0.5 parts of a lubricant;

[0062] Premixing the materials in the above proportions, and feeding the premixed materials into a twin-screw extruder for extrusion and granulation to obtain the alloy material;

[0063] The parameters of the twin-screw extruder are as follows: temperature settings: zone 1 120±10℃, zone 2 220±10℃, zone 3 230±10℃, zone 4 230±10℃, zone 5 240±10℃, zone 6 240±10℃, zone 7 240±10℃, zone 8 240±10℃, zone 9 245±10℃, die head 250±10℃; main engine speed: 30±3hz; feeding speed: 12±2hz; vacuum: -0.07±0.03MPa. Example 2

[0064] The difference between this embodiment and embodiment 1 is that: 40 parts of modified PMMA resin (obtained in preparation example 1);

[0065] The rest is exactly the same as in Example 1. Example 3

[0066] The difference between this embodiment and embodiment 1 is that: 60 parts of modified PMMA resin (obtained in preparation example 1);

[0067] The rest is exactly the same as in Example 1. Example 4

[0068] The difference between this embodiment and embodiment 1 is that: 50 parts of modified PMMA resin (obtained in preparation example 2);

[0069] The rest is exactly the same as in Example 1. Example 5

[0070] The difference between this embodiment and embodiment 1 is that: 50 parts of modified PMMA resin (obtained in preparation example 3);

[0071] The rest is exactly the same as in Example 1. Example 6

[0072] The difference between this embodiment and embodiment 1 is that: 50 parts of modified PMMA resin (obtained in preparation example 4);

[0073] The rest is exactly the same as in Example 1. Example 7

[0074] The difference between this embodiment and embodiment 1 is that: 50 parts of modified PMMA resin (obtained in preparation example 5);

[0075] The rest is exactly the same as in Example 1.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 1 is that: 50 parts of modified PMMA resin (obtained in Preparation Example 6);

[0078] The rest is exactly the same as in Example 1.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 1 is that: 50 parts of modified PMMA resin (obtained in Preparation Example 7);

[0081] The rest is exactly the same as in Example 1.

[0082] Comparative Example 3

[0083] The difference between this comparative example and Example 1 is that: 0 part of modified silicon dioxide;

[0084] The rest is exactly the same as in Example 1.

[0085] Comparative Example 4

[0086] A high-toughness and high-permeability PMMA-SAN alloy material, which comprises, by weight, 50 parts of PMMA resin, 35 parts of SAN resin, 2 parts of modified silica, 0.2 parts of a primary antioxidant, 0.4 parts of a secondary antioxidant, and 0.5 parts of a lubricant;

[0087] The preparation method is exactly the same as that in Example 1.

[0088] Results and Testing

[0089] The mechanical and optical properties of Examples 1-7 and Comparative Examples 1-3 were tested.

[0090] Tensile strength and elongation at break refer to: GB / T1040.1-2018 Determination of tensile properties of plastics, test conditions: 50mm / min;

[0091] Impact strength reference: GB / T1843-2008 Determination of plastic cantilever beam impact strength, test conditions: 5.5J;

[0092] Transmittance reference: GB / T2410-2008 Determination of light transmittance and haze of transparent plastics, test conditions: sample thickness: 4mm, 23℃;

[0093] The results are shown in Table 1.

[0094] Table 1

[0095]

[0096] From Table 1 and Examples 1-7, it can be seen that the alloy material prepared by the present invention has excellent performance in tensile strength, elongation at break, impact strength and light transmittance. Compared with the traditional PMMA-SAN material, it maintains a high degree of transparency while greatly improving the toughness of the alloy material.

[0097] By comparing Example 1, Comparative Examples 1 and 2, it can be seen that intermediate A and intermediate B play a very important role in the performance of the alloy material. Regardless of the lack of intermediate A (Comparative Example 1) or the lack of intermediate B (Comparative Example 2), the performance of the alloy material is significantly reduced. However, when the two are used at the same time, the performance of the alloy material is significantly improved, with a synergistic enhancement effect.

[0098] By comparing Example 1 and Comparative Example 3, it can be seen that, under the system of the present invention, the addition of a small amount of modified silicon dioxide significantly improves the overall performance of the alloy material, while the light transmittance remains good.

[0099] By comparing Example 1 and Comparative Example 4, it can be seen that compared with the traditional PMMA-SAN material, the alloy material prepared in the present invention has significantly improved overall performance while maintaining the transmittance.

[0100] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A PMMA-SAN alloy material with high toughness and high permeability, characterized in that: Calculated by weight, it includes 40-60 parts of modified PMMA resin, 30-40 parts of SAN resin, 1-3 parts of modified silica, 0.1-1 parts of primary antioxidant, 0.1-1 parts of secondary antioxidant, and 0.1-1 parts of lubricant; The modified PMMA resin is prepared by the following method: Polyethylene glycol-4000 and triethylamine are dispersed in a chloroform-acetone mixed solvent, and a mixed solution of methacryloyl chloride and chloroform is added dropwise to react to obtain an intermediate A; Dispersing p-toluene isocyanate, hydroxyethyl methacrylate, and a catalyst, dibutyltin dilaurate, in toluene, and reacting to obtain an intermediate B; The intermediate A, the intermediate B and methyl methacrylate are uniformly mixed, and azobisisobutyronitrile is added to carry out polymerization to obtain a modified PMMA resin; The preparation method of the modified silicon dioxide is as follows: Adding silicon dioxide to an ethanol aqueous solution, adding vinyltriethoxysilane, and heating to react, thereby obtaining modified silicon dioxide; The molar ratio of polyethylene glycol-4000, triethylamine and methacryloyl chloride is 1:(2.5-3.5):(1.8-2.2); The molar ratio of toluene isocyanate to hydroxyethyl methacrylate is 1:(0.95-1.05); The mass ratio of the intermediate A, intermediate B and methyl methacrylate is (20-40):(5-15):

100.

2. The high-toughness and high-permeability PMMA-SAN alloy material according to claim 1, characterized in that: The added amount of dibutyltin dilaurate is 1%-3% of the total mass of toluene isocyanate and hydroxyethyl methacrylate.

3. The high-toughness and high-permeability PMMA-SAN alloy material according to claim 1, characterized in that: The amount of azobisisobutyronitrile added is 0.1%-1% of the total mass of intermediate A, intermediate B and methyl methacrylate.

4. The high-toughness and high-permeability PMMA-SAN alloy material according to claim 1, characterized in that: The mass ratio of silicon dioxide to vinyl triethoxysilane is 1:(0.05-0.15).

5. The method for preparing the alloy material according to any one of claims 1 to 4, characterized in that: The steps include: The modified PMMA resin, SAN resin, modified silicon dioxide, a primary antioxidant, a secondary antioxidant and a lubricant are premixed, and the premixed materials are sent to a twin-screw extruder for extrusion granulation to obtain the alloy material.

6. The method for preparing the alloy material according to claim 5, characterized in that: The parameters of the twin-screw extruder are as follows: temperature settings: zone 1 120±10℃, zone 2 220±10℃, zone 3 230±10℃, zone 4 230±10℃, zone 5 240±10℃, zone 6 240±10℃, zone 7 240±10℃, zone 8 240±10℃, zone 9 245±10℃, die head 250±10℃; main engine speed: 30±3Hz; feeding speed: 12±2Hz; vacuum: -0.07±0.03MPa.

Citation Information

Patent Citations

  • Transparent optical material with high impact resistance and high heat resistance and preparation method thereof

    CN114539701A

  • High-flow high-impact modified PMMA / ASA material and preparation method thereof

    CN117004159A